Evaluation of the Effectiveness of Mobile Health Technology in Promoting Positive Behavioral Change Among School of Education Students at Kenya Methodist University - Patel, Harshika Naginbhai; Njoki, Vanessa; Majuma, Magdaline; Cherono, Sheilla; Andanje, Marion; Shonko , Martin (International Journal of Professional Practice, 2026)
The growing popularity of mobile phones has led to the development of an interdisciplinary branch of the healthcare profession known as mobile health (mHealth). As convenient devices with internet access become more widely available, mHealth technology has sparked interest among health professionals in delivering quality care. This study evaluates the effectiveness of mHealth technology in promoting positive behavioral change among students in the School of Education at Kenya Methodist University. It sheds light on mHealth, assesses its effectiveness, and establishes its usefulness in medical practice.The research adopted a cross-sectional survey; a sample size of 384 participants was derived using Fisher’s formula from a population of 2,489. A simple random sampling technique was employed to collect data using a structured, pre-tested questionnaire. Ethical clearance was obtained from the Kenya Methodist University Ethical Committee Review Secretariat. Collected data were analyzed using descriptive statistics and represented graphically.The study consisted of more male (58.07%) than female (41.93%) participants, with the majority in their fourth year (n = 132). While 25% of the population were connected to health systems, 75% were not. 93.2% of respondents used internet sites, such as PubMed, or mobile apps, such as the Flow app, as their preferred intervention. More than 50% of students reported that these interventions efficiently promote and sustain positive health behaviors. Lack of engagement and internet access were the significant challenges identified.In conclusion, this research found strong evidence supporting the effectiveness, acceptability, and dependability of mHealth interventions in promoting behavioral change. This study recommends that increasing awareness, particularly in evaluating mHealth for chronic illnesses like diabetes, will eventually decrease mortality and morbidity. This will help policy-makers create better medical interventions.